PENGARUH PENERAPAN BAURAN PEMASARAN DIGITAL TERHADAP MINAT BELI PENGGUNA KERETA API MELALUI APLIKASI MOBILE KAI ACCESS - Jayabaya, Petrus; Madiawati, Putu Nina (JURISMA : Jurnal Riset Bisnis & Manajemen, 2018)
Digital Marketing Mix is one of the elements used as a tool for marketing the products toward consumers with an effort to stimulate interest in each consumer to make a purchase. The research is conducted to determine the effect of the application of digital marketing mix to the purchase intention of train user through KAI ACCESS mobile application. This research method is descriptive quantitative. As for the sampling used is probability sampling with simple random sampling type, which the number taken 100 respondents. This study uses multiple linear regression analysis. The result of research that is, digital marketing mix variable simultaneously influence the variable of purchase intention. The digital marketing mix is positively influential and significant to the variable of buy interest, where the contribution of 93.32%, the rest of 6.7% is the influence of other factors. The conclusion obtained that the factors that influence the purchase intention of train users from the digital marketing mix are Product, Promotion, Price, Person, Process, and Physical Evidence, while Place is not. The advice given to the company is to maintain the elements of the digital marketing mix considered good by consumers.Â Keywords: digital marketing mix, purchase intention.